Epidemiological Study of Canine Parvoviral Enteritis in Jaipur, Rajasthan - Mandawat, Saksham; Singh, Rashmi; Mohammed, Nazeer; Singh Meena, Dharm; Jyoti; Chaudhary, Warsha; Kumar Meena, Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Canine Parvo Virus (CPV) is a major cause of morbidity and mortality in young dogs globally. The epidemiological study was conducted in Jaipur, Rajasthan (India) to assess the occurrence of CPVE and its association with climatic and host-related risk factors over a six month period (July to December 2024). A total of 200 faecal samples from clinically suspected dogs were tested using PCR, revealing an overall CPV positive rate of 83% (166/200). Month-wise analysis demonstrated a significant decline in positivity rate from July (96.7%) to December (10.0%), correlating with climatic temperature. Statistical analysis confirmed significant associations (p
Keywords: Canine parvovirus; Climatic risk factors; Epidemiology; Seasonal variation; Vaccination